Ethical Considerations in Maritime Technology and Marketing Management: A Framework for Responsible Decision-Making - Tegar Sangga Buana; Teguh Budiaji; Trisna Mahendra; Zahra Citra Ayu; Zaqia Azzarine (Harmony Management: International Journal of Management Science and Business, 2025)
The rapid advancements in technology and marketing strategies within the maritime industry present both opportunities and ethical challenges. While innovation enhances operational efficiency and consumer engagement, the absence of structured ethical frameworks can lead to privacy violations, regulatory breaches, and deceptive marketing practices. This study examines the role of ethical considerations in technology and marketing management within maritime leadership, emphasizing the need for structured ethical decision-making frameworks to ensure consumer protection, regulatory compliance, and corporate sustainability. This research provides original value by assessing the extent to which ethical principles are integrated into maritime business strategies, addressing gaps in previous research that primarily focuses on profitability over ethical governance. The study explores the following research questions: How do ethical considerations shape decision-making in maritime technology and marketing management? What challenges hinder the implementation of structured ethical frameworks? Using qualitative research methods, semi-structured interviews with industry experts, lecturers, and postgraduate students were conducted, followed by thematic analysis and comparative evaluation. Findings indicate that while ethical decision-making enhances corporate reputation and regulatory compliance, industry-wide implementation remains inconsistent due to weak regulatory enforcement and corporate reluctance. The study concludes that integrating ethical frameworks into maritime leadership training and business education is essential for fostering responsible corporate governance, enhancing consumer trust, and ensuring long-term sustainability.